Pengolahan Limbah Kotoran Burung Puyuh Menjadi Kompos untuk Petani di Desa Gampeng, Gampengrejo, Kabupaten Kediri - Tanjungsari, Ardina; Utomo, Budi; Andaruisworo, Sapta; Yuniati, Erna; Solikin, Nur; Anifiatiningrum, Anifiatiningrum (Universitas Nusantara PGRI Kediri, 2023)
Quail waste from Omah Puyuh Kediri is usually disposed without being processed, it can be smells odor and environmental pollution. Lecturers and students of the Animal Husbandry Study Program UNP Kediri through Community Service activities aimed providing insight and skills to students and the community in Gampeng Village, Gampengrejo, Kediri Regency by processing quail manure into compost is the right solution. During this pandemic, the availability of chemical fertilizers is increasingly rare and expensive. The composting of quail was made through short training using simple and easy materials. The targets in this activity are students, breeders, and farmers to add insight and skills to process quail waste into compost so that it can be used by farmers. This activity was attended by 30 participants from students, breeders, and farmers. This activity is divided into two stages, namely training and hands-on practice. The training was provided through the delivery of material on the meaning, method of making, and the benefits of compost. Then continued the practice of making compost. The results showed the enthusiasm of the participants in participating in the training, and the participants were able to practice making compost well. The results of the questionnaire on the satisfaction level of participants showed that the community service activities organized by lecturers and students of the Animal Husbandry Study Program UNP Kediri were very satisfying.